Preliminary discussion on the earthquake early warning network of Jiangxi Province - Si Yu; Tingting Tang (地震科学进展, 2021)
The earthquake early warning system is formed by seismic stations and the urgent information systems. Many seismic stations are added to the original seismic monitoring network and old operation systems are upgraded. Early warning and emergency earthquake information to the public and government departments can be published rapidly. This article introduces the earthquake early warning network of Jiangxi Province and evaluates the seismic monitoring capability.